Impaired antipneumococcal activity of bronchoalveolar lining material of neonatal rats. - Coonrod, J D (1989)
Pulmonary clearance of inhaled pneumococci is markedly impaired in neonatal rats compared with that in adult rats. To determine whether this impairment is due to a deficiency of extracellular bactericidal factors, the antipneumococcal activity of free fatty acids (FFA) in lung surfactant and the levels of lysozyme and transferrin in lavage fluids were quantified. Surfactant from adult rats averaged 68 U of antipneumococcal activity per g (dry weight) of lung, compared with less than 0.25 U for rats less than 1 week old (P less than 0.001). The kinds of FFA in surfactant of neonatal and adult rats were essentially identical, and the antipneumococcal activity of highly purified FFA from surfactant of neonatal and adult rats was also the same. However, the quantity of FFA in surfactant varied significantly with age, and rats less than 3 weeks old had much lower levels of surfactant FFA than did adults (P less than 0.001). In addition, lavage fluids from neonatal rats inhibited the antipneumococcal activity of surfactant FFA more than lavage fluids from adults did (P less than 0.02). This inhibitory activity did not appear to be due to protein binding. Lavage fluids from neonates showed an age-related deficiency of lysozyme (P less than 0.001), but lysozyme appeared to play no role in pneumococcal killing by the surfactant fraction of lavage fluids in vitro. Transferrin levels in lavage fluids were similar for neonates and adults. It was concluded that lung surfactant from neonatal rats was deficient in antipneumococcal activity, due mostly to low levels of FFA and to a lesser degree to increased levels of inhibitor(s) in lavage fluids.